Implementation of Loading and Unloading Service Policy at Bitung Port - Koloay, Roby Albert; Kairupan, Sisca; Tumbel, Goinpeace (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The purpose of this research is to explain how the implementation of the loading and unloading service policy at Bitung Port.The research method uses a qualitative approach. Data collection techniques using interviews, documentation studies and observation. The results found that by increasing supervision of the implementation of loading and unloading performance of goods and containers, it is possible that there is no idle time. Supervising the performance of tools and checking and repairing loading and unloading tools, namely container cranes so that when used for loading and unloading activities do not experience damage which results in idle time and also has an impact on loading and unloading productivity.